KEKUASAAN PRESIDEN (Studi Komparatif RI dengan Beberapa Negara Maju) - Abdul Ghoffar (Widyariset, 2010)
The Presidential power after the amandment of 1945 Constitution has decreased. Many people think thatsuch decreases are excessive because in practice, majority of the president’s policy requires approval of the Parliementary,making the President has difficulty in running the government. To avoid confusion, the researcher isinterested in conducting research related to the presidential power of the President of Indonesia compared to thepower of head of state/and or head of government in eight developed countries, namely the United States, Russia,Japan, China, Kuwait, Australia, and South Africa. In conducting the research, the researcher uses reseach methodsof juridicial, historical and comparative approaches. The result of this study indicates that Indonesian Presidentialpower is quite enormous compared to the power owns by the head of states and / or head of governments in theabove mentioned countries. Only Kuwait Amir’s power can defeat Indonesian Presidential power. The power ofKuwait Amir is similar to Indonesian Presidential power before 1945 Constitution amandment.